Increasing Expression of PnGAP and PnEXPA4 Provides Insights Into the Enlargement of Panax notoginseng Root Size From Qing Dynasty to Cultivation Era - Yu, Mu-Yao; Hua, Zhong-Yi; Liao, Pei-Ran; Zheng, Han; Jin, Yan; Peng, Hua-Sheng; Cui, Xiu-Ming; Huang, Lu-Qi; Yuan, Yuan (Frontiers in Plant Science, 2022)
Root size is a key trait in plant cultivation and can be influenced by the cultivation environment. However, physical evidence of root size change in a secular context is scarce due to the difficulty in preserving ancient root samples, and how they were modified during the domestication and cultivation stays unclear. About 100 ancient root samples of Panax notoginseng, preserved as tribute in the Palace Museum (A.D. 1636 to 1912, Qing dynasty), provided an opportunity to investigate the root size changes during the last 100 years of cultivation. The dry weight of ancient root samples (~120 tou samples, tou represents number of roots per 500 g dry weight) is 0.22-fold of the modern samples with the biggest size (20 tou samples). Transcriptome analysis revealed that PnGAP and PnEXPA4 were highly expressed in 20 tou samples, compared with the 120 tou samples, which might contribute to the thicker cell wall and a higher content of lignin, cellulose, and callose in 20 tou samples. A relatively lower content of dencichine and higher content of ginsenoside Rb1 in 20 tou samples are also consistent with higher expression of ginsenoside biosynthesis-related genes. PnPHL8 was filtrated through transcriptome analysis, which could specifically bind the promoters of PnGAP, PnCYP716A47, and PnGGPPS3, respectively. The results in this study represent the first physical evidence of root size changes in P. notoginseng in the last 100 years of cultivation and contribute to a comprehensive understanding of how the cultivation environment affected root size, chemical composition, and clinical application.